Raising Awareness and Lowering Rates of Sexual Assault on East Carolina University’s Campus and Surrounding Areas - Stox, Logan Caroline (East Carolina University, 2022)
Comprehensive writing about the struggles, successes, and blockages that our group worked through during our Signature Honors Project. The sexual assault prevention campaigns, actions, and changes we made or attempted to make during this time are laid out in a semesterly basis, with my personal reflection on our achievements and mistakes.
Face to Face: It's Personal
Keywords: sexual assault prevention, sexual assault, LiveSafe, Student Safety Committee